Kísérlet a poena extraordinaria egy jelentésének feltárására a 18. század második felének debreceni ítélkezési gyakorlatában - Biczó, András (Debreceni Jogi Műhely, 2017)
In my essay I analyze a possible semantic content of poena extraordinaria. Int the first part of the study can be found on interpretation concerning the different meanings of poena ordinaria and poena extraordinaria. In my hypothesis I suppose if the crime hasn't been entirely proved by accuser then the judge has to apply the category of poena extraordinaria. I examine three criminal brief of cases from Debrecen at 18th century in the second part; trying to verify my hypothesis.